The Urgency of Strengthening Pretrial Mechanisms in Controlling Coercive Measures within the Indonesian Criminal Justice System - Imron Rosyadi (Journal of Law, Politic and Humanities, 2026)
This study is grounded in the growing concern over the limited effectiveness of pretrial mechanisms in supervising coercive measures exercised by law enforcement, which may lead to violations of individual rights and abuse of authority. The research aims to analyze normative weaknesses in the regulation of pretrial proceedings and to formulate a strengthened model of judicial control within the Indonesian criminal justice system. This study employs a normative legal research method using statutory, conceptual, and case approaches, with legal materials derived from primary sources such as the Criminal Procedure Code, relevant laws, and constitutional court decisions, as well as secondary legal literature, all examined through a normative and interpretative legal analysis. The results indicate that despite the expansion of pretrial objects through constitutional interpretation, significant gaps remain in evidentiary standards, judicial authority, and procedural safeguards. This research offers a novel framework by proposing a more substantive and procedural strengthening of pretrial mechanisms aligned with the principles of due process of law. It concludes that reinforcing pretrial institutions is essential to ensure legal accountability and the protection of fundamental rights within the criminal justice system.